Effect of oxathiapiprolin on asexual life stages of Phytophthora capsici and disease development on vegetables. (2nd December 2014) - Ji, P.; Csinos, A.S.
Abstract Phytophthora blight caused by Phytophthora capsici is a serious disease in the production of peppers and other vegetables worldwide. Application of fungicides is an important component in developing effective disease management programmes. However, resistance in P. capsici populations to some commonly used fungicides has been documented. Identification of effective new fungicides with different mode of actions is highly desirable. This study was conducted to determine baseline sensitivity of P. capsici isolates to oxathiapiprolin, the first member of a new class of isoxazoline fungicides, and efficacy of this compound for reduction of Phytophthora blight on bell pepper. A collection of 126 P. capsici isolates were evaluated and all the isolates were sensitive to oxathiapiprolin. EC50 values of oxathiapiprolin in inhibiting mycelial growth, sporangium formation and zoospore germination of 25 selected isolates averaged 0.001, 0.0003 and 0.54 µg mL−1, respectively. It appeared that asexual life stages of P. capsici were more sensitive to oxathiapiprolin than other compounds used for control of oomycete pathogens. In field studies, oxathiapiprolin applied at different rates through drip irrigation tubes, or by soil drench plus foliar sprays, reduced Phytophthora blight and increased pepper yield significantly. This is the first report of the efficacy of oxathiapiprolin in suppression of P. capsici, which indicates that oxathiapiprolin is effective in inhibiting the pathogen and has the promise to be a viable option for managing Phytophthora blight in bell pepper production.